Informed Consent Reformulation by Health Personnel in Health Services - Dian Lukita Sari; Arief Suryono; Isharyanto Isharyanto (Masters Program in Public Health, Sebelas Maret University, 2018)
Background: Informed consent is an approval given after receiving information. The arrangement of informed consent is more emphasized on the medical act, namely the Minister of Health Regulation no. 290 of 2008 on Approval of Medical Measures, whereas in addition to doctors / dentists including health personnel must also obtain the consent of the patient. Article 68 paragraph (6) of Law no. 36 of 2014 on Health Manpower explaines that the procedures for approval of the Health Manpower Act are regulated by Ministerial Regulation, but until now none of it existed. Therefore, it is necessary to reformulate informed consent to provide legal certainty for all health personnel.Subjects and Methods: Normative type study with statute approach that is legislation and conceptual approach, technique of collecting law material with literature study. Technical analysis of legal materials was done by formulating legal principles, formulating legal understanding and formation of legal standards.Results: Urgency of reformed informed consent in health service action for health personnel viewed from the perspective of legislation that is Law no. 36 Year 2009 on Health, Law no. 44 Year 200 on Hospital, Law no. 36 of 2014 on Health Manpower and Regulation of the Minister of Health RI No. 69 of 2014 on Hospital Obligations and Patient Obligations explained that informed consent is provided by health personnel. Urgency due to social interests in the matter of public security as well as social interests concerning the lives of individuals. Urgency of legal certainty that the law can be implemented properly if there is adequate regulation and equal treatment before the law. Ideal informed consent reform as the implementation of Article 68 paragraph (6) of the Law on Health Manpower needs to re-regulate Regulation of the Minister of Health Number 290 Year 2008 regarding Approval of Medical Measures. Reformulation of preliminary consideration and consideration considering the adjusted development of science as well as legal subjects informed consent uniformed into health personnel.Conclusions: The urgency of reformulating informed consent is because in the therapeutic agreement, it is the fulfillment of the principle of consensualism in the agreement; for the social interest in public security matters and concerning the lives of individuals and need the latest regulation for legal certainty for all health personnel. Ideal informed consent reform is the needs to reorganize the Approval of Health Personnel Act by substituting Regulation of the Minister of Health No. 290 Year 2008 on Approval of Medical Measures, by changing the subjects for